Islamic Religious Education (PAI) Learning Assessment Based On Higher Order Thinking Skills (HOTS) At SMK Muhammadiyah 5 Jember - Isnaini, Nur; Jannah, Nur (AL-WIJDÃN Journal of Islamic Education Studies, 2024)
Teachers' lack of understanding of the HOTS assessment concept and how to integrate it into learning assessment is a crucial problem that needs to be resolved. This research reveals the HOTS-based PAI learning assessment implementation at SMK Muhammadiyah 5 Jember. The aim is to explore and evaluate the effectiveness of using HOTS in assessing Islamic religious education (PAI) learning at this institution. Using a qualitative phenomenology-type approach involving observation, interviews, and document study. The research results show that 1). The formulation of learning objectives uses learning achievement (CP) references developed in learning objectives with high-level thinking indicators. 2). Assessment instruments are carried out by student competencies. 3). Use of a problem-based learning model (Problem-Based Learning) which was developed with several types of innovative learning strategies. 4) Creative tasks can improve high-level thinking skills as demonstrated by the behavior of appreciating explanations, being able to interpret actual problems, and generating new ideas by thinking critically and creatively.   Keywords: Assessment, PAI Learning, Higher Order Thinking Skills (HOTS)